Systemic Immune Dysregulation Correlates With Clinical Features of Early Non-Small Cell Lung Cancer - Hao, Zhixing; Lin, Mingjie; Du, Feng; Xin, Zhongwei; Wu, Dang; Yu, Qun; Wu, Yimin; Zhu, Zhouyu; Li, Wenshan; Chen, Yongyuan; Chen, Xiaoke; Chai, Ying; et al. (Frontiers in Immunology, 2022)
Background: Systemic immune dysregulation correlates with cancer progression. However, the clinical implications of systemic immune dysregulation in early NSCLC remain unclear. Methods: Using a panel of 9 markers to identify 12 parameters in the peripheral blood of 326 patients (34 in the discovery group and 292 in the validation group), we investigated systemic immune dysregulation in early NSCLC. Then, we analyzed the impact of surgery on the systemic immune state of these patients. Finally, we analyzed correlations between systemic immune dysregulation and the clinical features of early NSCLC. Results: We found striking systemic immune dysregulation in the peripheral blood of early NSCLC patients. This dysregulation was characterized by a significant decrease in total lymphocytes, T cells, quiescent T cells, CD4+ T cells, and NKT cells. We also observed increased proportions of activated lymphocytes and activated T cells. Systemic immune dysregulation was increased after surgery. Furthermore, systemic immune dysregulation was correlated with multiple clinical features, such as sex, age, smoking history, pathological type, tumor stage, surgical approach, tumor differentiation, and epidermal growth factor receptor (EGFR) mutation. Finally, we observed that systemic immune dysregulation was correlated with complications and systemic inflammatory response syndrome (SIRS) in early NSCLC patients. Conclusions: Our results reveal systemic immune dysregulation occurring in early NSCLC and demonstrate the correlation between these dysregulation and clinical features. Our findings suggest that systemic immune dysregulation is involved in cancer development and may be a promising candidate for high-risk screening and treatment strategies for early NSCLC.